A novel avalanche-confinement TEPC for microdosimetry at nanometric level. (August 2017) - Bortot, D.; Pola, A.; Agosteo, S.; Pasquato, S.; Mazzucconi, D.; Fazzi, A.; Colautti, P.; Conte, V.
Abstract: The tissue equivalent proportional counter (TEPC) is the most accurate device for measuring the microdosimetric properties of a particle beam, showing to assess the relative biological effectiveness by linking the physical parameters of the radiation field with the corresponding biological response. Nevertheless, no detailed information on the track structure of the impinging particles can be obtained, since the lower operation limit of the common TEPCs is about 0.3 μm. On the other hand, the pattern of particle interactions at the nanometer level, which demonstrated to have a strong correlation with radiation-induced damages to the DNA, is measured directly by only three different nanodosimeters worldwide: practical instruments are not yet available. The gap between microdosimetry and track-nanodosimetry can be filled partially by extending the TEPC response down to the nanometric region. A feasibility study of a novel TEPC designed to simulate tissue-equivalent sites in the nanometric domain was performed. The present paper aims at describing the design, the development and the characterization of this avalanche-confinement TEPC. Irradiations with photons, fast neutrons and low-energy carbon ions demonstrated the capability of this TEPC of measuring in the range 0.3 μm–25 nm. Highlights: A low-pressure avalanche-confinement TEPC for the simulation of nanometric sites. Compact and removable Cm-244 alpha source embedded in the TEPC sensitive volume. Coincidence with a miniaturized internal SSD to perform lineal energy calibration. Measurements of the TEPC response against photon and fast neutron fields. Test with a 62 AMeV carbon ion beam at site sizes in the range 300–25 nm.